Latent Syphilis Infection in Pregnancy: An Ultrasound Diagnosed Case of Penicillin Treatment Failure - Lucia Pasquini; Elena Rita Magro-Malosso; Adalgisa Cordisco; Michele Trotta; Mariarosaria Di Tommaso (Case Reports in Obstetrics and Gynecology)
We report a case of early latent syphilis (reactive serologic tests without clinical evidence of disease within 24 months from the onset of the infection) in pregnancy. Despite an appropriate maternal treatment with benzathine penicillin G, sonographic signs of fetal syphilis were detected. Follow-up scans, in addiction to serial serological tests, have allowed the identification of fetal infection and therefore the failure of antibiotic therapy. We highlight the importance of ultrasound in suspecting fetal infection and in evaluation of the fetal response after penicillin treatment.